Advocacy Compromised: How Financial, Organizational and Institutional Factors Shape Advocacy Strategies of Civil Society Organizations - Arvidson, Malin; Johansson, Håkan; Scaramuzzino, Roberto (Voluntas (Manchester, England), 2018)
Key functions of civil society organizations (CSOs) are to criticize governments and to hold them to account. Recent trends of privatization and contracting out challenge CSOs' opportunities to voice such criticism. The purpose of this article is to analyse whether and why CSOs 'hold back their criticism' of public authorities, and how a compromised advocacy can be linked to financial, organizational and institutional factors. The article draws on an original survey of 2678 Swedish CSOs. The analyses show that certain levels of funding make CSOs more likely to hold back in their criticism, but also organizational and institutional factors play a role. The results identify the importance of distinguishing between objective and subjective factors related to how dependency is framed. It is the felt needs, experiences and perceptions of CSOs themselves that make hem prone to the strategic choice to hold back criticism of public authorities.